PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS I-SPRING SUITE MATERI IPA KELAS V DI SDN BENDOSARI 01 KAB. TULUNGAGUNG - Silvia Auliya; Wahyudi; Muhamad Basori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research develops learning media based on i-Spring Suite becausein the learning process, teachers have not maximized the use of learning media and classroom management. learning media and classroom management. So this media is intended to provide new innovations in the learning process and can help teachers in delivering material information easily and fun. This study aims to improve students' abilities, especially on water cycle material. The research method uses the ADDIE model (Analysis, design, development, implementation, and evaluation). The research subjects were fifth grade students at SDN Bendosari 01 Tulungagung Regency, totaling 32 students. The results of the research on the validity test obtained results in the validity test of media experts and material experts obtained a percentage of 90% very valid category. The effectiveness test in the limited trial obtained 100% classical learning completeness results and the broad trial obtained 95.45% classical learning completeness results in the very effective category. Practicality test on teacher response questionnaire 96% very practical category and practicality test on student response questionnaire 93.12% very practical category. These results state that i-Spring Suite-based learning media is suitable for use in learning.